2020
DOI: 10.21597/jist.642503
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Autonomous Surface Vehicle for Inland Water

Abstract: This paper considers the design and implementation of a low-cost and modular autonomous surface robot for inland water. The design process consists of three stages: Mechanical and electro-mechanical design, electrical and electronic design and software design. The mechanical design is based on a two-hull construction because of its low risk of capsizing in rough water. Off-the-shelf hulls and electric trolling motor are preferred to reduce the cost. The robot is steered by a rudder controlled by a servo motor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The current literature provides detailed ASV’s state of the art like [ 9 , 10 ] or, more recently, [ 11 , 12 ]. Regarding research and development, several relevant projects have been reported, carrying out different operations in aquatic scenarios like in [ 13 , 14 , 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…The current literature provides detailed ASV’s state of the art like [ 9 , 10 ] or, more recently, [ 11 , 12 ]. Regarding research and development, several relevant projects have been reported, carrying out different operations in aquatic scenarios like in [ 13 , 14 , 15 ].…”
Section: Related Workmentioning
confidence: 99%